Pengajaran Tafsir di Dayah Terpadu Al-Muslimun, Aceh Utara: Analisis Sejarah, Metode Pengajaran dan Pengaruhnya - Rousydiy Rousydiy (Majalah Sainstekes, 2018)
The Islamic education is became considerable concern in Aceh from time to time and Dayah is one of the educational institution model which teaches the Quran. The weaknesses of the students both in reading and understanding the contents of Quran affected the goals and learning objectives, therefore the method of teaching is the key of learning achievement for individual who love the Quran. This study aims to identify the design and historical Tafsir studies at Dayah in Indonesia and in Aceh and analyzing the teaching method used and to know the extent influence of the methods practiced at integrated Dayah Al-Muslimun in North Aceh. A qualitative study was employed to collect the data from the respondents. A semi structure interview was conducted from four subjects’ teachers to explore the influence of the teaching method at Dayah Al-Muslimun Aceh. The result of study showed that the history of Tafsir studies at Dayah in Indonesia cannot be separated from the history of early spreading Islam in the Malay Archipelago. Moreover, the majority of Tafsir’s teachers at integrated Dayah Al-Muslimun used translation method and telling story in their teaching method. In term of interpretation of verse the majority of teachers used “tahlili methods” (problem solving). The impact of learning Tafsir was reviewed from three aspects, namely understanding, practice, and the result of examination. Moreover, this study emphasized that the teaching methods used for teaching Tafsir are good and have a good influence on students, this proven from the good aspect of understanding, the appropriate practice and the result of examination, however it still need to be evaluated and improved.